P872 BaiCD gene abundance is negatively correlated with Clostridium difficile infection. (16th January 2018) - Solbach, P; Woltemate, S; Chhatwal, P; Tacconelli, E; Buhl, M; Gerhard, M; Vehreschild, M; Jazmati, N; Rupp, J; Manns, M P; Bachmann, O; Suerbaum, S
Abstract: Background: Clostridium difficile infection (CDI) poses an increased risk to patients with inflammatory bowel disease. Preconditions are colonisation with C. difficile, but also a breakdown of the colonisation resistance, of which secondary bile acids are believed to constitute a decisive component. 7α-dehydroxylation is one of the key steps in primary to secondary bile acid transformation, and required genes have been located in a single bile acid inducible ( baiCD ) operon in C. scindens as well as in C. hiranonis . The prevalence of these species in human fecal samples—particularly with regard to samples tested positive for C. difficile —and in the setting of fecal microbiota transfer (FMT) in CDI patients has not been studied. Methods: A species-specific qPCR for detection of baiCD in C. scindens and C. hiranonis was established. Fecal samples of patients with CDI, toxigenic C. difficile colonisation (TCD), non-toxigenic C. difficile colonisation (NTCD), of C. difficile negative (NC) patients, and of two patients before and after fecal microbiota transfer (FMT) for recurrent CDI (rCDI) were tested for the presence of the baiCD gene cluster. Results: In NC samples, the prevalence of the baiCD gene cluster was significantly higher than in CDI samples, with 72.5% (100/138) vs. 35.9% (23/64; p < 0.0001), respectively. No differences were seen between NC compared with NTCD samples or TCD samples. Both rCDI patients were baiCD negative at baseline, but one patient turned positive after successful FMT from a baiCD positive donor. BaiCD /16S rDNA ratio calculation showed no significant difference between the relative abundances in both groups (NC vs. CDI; p = 0.3244). The median of the NC group was 0.006% (IQR 0.0005%-0.376%) and for the CDI group 0.009% (IQR 0.0002%-7.8%). In addition, stool consistency did not measurably influence the relative abundance of bacterial species in this context of complex microbial communities. Conclusions: BaiCD gene positive species are reduced in fecal samples of patients with C. difficile infection as compared with asymptomatic carriers or C. difficile negative fecal samples. Furthermore, we present a case of baiCD gene positivity observed after successful fecal microbiota transfer for recurrent CDI.